Coding reliability and agreement of International Classification of Disease, 10th revision (ICD-10) codes in emergency department data. (2018) - Peng, Mingkai; Eastwood, Cathy; Boxill, Alicia; Jolley, Rachel Joy; Rutherford, Laura; Carlson, Karen; Dean, Stafford; Quan, Hude
No abstract available